Critical psychology praxis : psychosocial non-alignment to modernity/coloniality - Beshara, Robert K. (Abingdon ; New York : Routledge, 2021)
"This collection of chapters advances critical psychology by incorporating praxis (theory and practice) and decolonial streams of thought. They are united around a theme of psychosocial non-alignment to modernity/coloniality. Bringing together a transdisciplinary range of authors from around the world, this edited volume weaves together a spectrum of complex arguments and perspectives to lay the foundations for bridging the Global North-South divide in critical psychology through solidarity and dialogue. The book's central argument is to emphasize praxis and transdisciplinarity over disciplinary fundamentalism. Psychology is only a starting point and not the end goal of critique in this book; incidentally, some of the authors are not even psychologists. Instead, the book draws on decolonial theoretical resources, such as Chican@ Studies, Black Male Studies, and Critical Pedagogy, to complement traditional theoretical resources like psychoanalysis, Marxism, poststructuralism, and feminism. This groundbreaking text is suitable for scholars and upper-level undergraduate and postgraduate students studying critical discourse, the psychology and philosophy of post-coloniality, conceptual and historical issues in psychology, as well as anthropology and sociology courses engaging with action research"--
OCLC-licensed vendor bibliographic record.
Keywords: Critical psychology; Decolonization; Intersectionality (Sociology); Social sciences; PSYCHOLOGY / General